Upaya peningkatan pengetahuan keluarga untuk mencegah hiperglikemi pada ny. S di desa baki - Ibnu Pratama, Muchibulloh; , Vinami Yulian, Ns., M.sc.Nursing (2016)
Diabetes mellitus is a chronic disease , held for life and occurred because that there are problems in insulin characterized preventing disturbances metabolism of carbohydrates , proteins and fats . So need to an awareness in people with it self and the role of family in treating a member of his family who suffered diabetes mellitus and also the role of a nurse to reducing the complication in people with diabetes mellitus.The purpose of this research is to know the relationship between knowledge family in preventing hiperglikemi in people with diabetes mellitus. Method this research uses the method descriptive namely by fact-finding to the interpretation of proper , methods to make descriptions of situations in patients and collected the data based on existing facts and truth , through case study. The results showed no significant relationship between knowledge and handling to prevent hyperglycemia in patients with diabetes mellitus. From the knowledge it will evolve into awareness of how dangerous the family of diabetes mellitus later the family able to care for and make decisions that tepat.Perubahan lifestyle is difficult but nothing is impossible because anything can be changed while there is a will and effort. Family knowledge is one of the keys to change the wrong lifestyle. Awareness for change will happen over time.